Developing post-pandemic livable and sustainable cities: providing space for urban activities in bandung - Iman, Hanafi Kholifatul; Tsana, Shafwatus; Febriani, Nurindah; Prilandita, Niken; Fatmadewi, Rose (Universitas Gadjah Mada, 2024)
Providing space for urban activities and preserving the environment are contradictory issues in urban development, including Bandung City, which COVID-19 exacerbates. With limited carrying capacity, the impact of COVID-19, and high levels of urban activity, there are issues regarding the impact of urban activity on the quality of the post-pandemic urban environment. Therefore, it is necessary to research the limitation of Bandung City's carrying capacity to accommodate post-pandemic urban activities. This research aims to formulate a post-pandemic development concept and framework for Bandung City based on the environment's ability to accommodate urban activities. The approach and analytical method used in this research is descriptive-qualitative analysis, which can explore and focus on deepening the literature used as a basis for drafting the concept. In general, this research results in the concept of a livable and sustainable post-pandemic development, including formulating indicators for Bandung that reflect what Bandung City needs to develop after the pandemic. This research is quite important because it can see the characteristics of Bandung City and formulate its development by the conditions of Bandung City so that the government or planner can use these results as evaluation material or suggestions for the Bandung City and West Java Provincial Government in monitoring and evaluating the implementation of strategies, policies, and programs inappropriate development with environmental capacity in the Bandung Basin Urban Area and North Bandung Area.